2021
DOI: 10.1145/3529162
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Scalability Modeling of QoS-aware Dynamic Service Composition

Abstract: In Dynamic Service Composition(DSC), an application can be dynamically composed using web services to achieve its functional and Quality of Services (QoS) goals. DSC is a relatively mature area of research that crosscuts autonomous and services computing. Complex autonomous and self-adaptive computing paradigms (e.g. multi-tenant cloud services, mobile/smart services, services discovery and composition in intelligent environments such as smart cities) have been leveraging DSC to dynamically and adaptively main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While open data has numerous advantages, it also comes with its share of disadvantages and challenges [35]. This literature review explores the disadvantages of open data as identified in academic research and practical applications [36]. Privacy concerns, data quality issues, security risks, potential misuse, the digital divide, and resource constraints are among the key disadvantages associated with open data.…”
Section: Open Data Disadvantagesmentioning
confidence: 99%
“…While open data has numerous advantages, it also comes with its share of disadvantages and challenges [35]. This literature review explores the disadvantages of open data as identified in academic research and practical applications [36]. Privacy concerns, data quality issues, security risks, potential misuse, the digital divide, and resource constraints are among the key disadvantages associated with open data.…”
Section: Open Data Disadvantagesmentioning
confidence: 99%
“…In fact, the QoS-aware service composition has been widely explored for Web services or cloud services in the service computing field [9][10][11][12][13][14]. By reviewing the literature, the techniques for QoS-aware service composition can be classified into four categories: local maximization approaches, linear optimization approaches, approximation approaches, and Pareto-optimization approaches [15].…”
Section: Related Workmentioning
confidence: 99%
“…QoS-aware service recommendation is an important subproblem in the service computing field and can be regarded as a QoS-aware service selection optimization problem. The existing research work can be categorized as follows: utility-based methods [26][27][28], Skyline-based methods [12,13,29], collaborative-filtering-based methods [14,15], matrix-factorization-based methods [16,17,30], and factorization-machine-based methods [18,19,31]. Next, we introduce these methods and their application scenarios from the perspective of their advantages and disadvantages.…”
Section: Related Workmentioning
confidence: 99%